CLINICAL UTILITY OF CYFRA 21-1 IN ONCOLOGY: A COMPREHENSIVE REVIEW OF CURRENT EVIDENCE AND FUTURE DIRECTIONS - Paweł Jurczak; Dominik Małek; Paweł Puczel; Marta Siwek; Klaudia Sztaba (International Journal of Innovative Technologies in Social Science, 2025)
CYFRA 21-1, a soluble fragment of cytokeratin-19 released during epithelial cell apoptosis and necrosis, has emerged as a promising serum biomarker across a wide range of epithelial malignancies. This review synthesizes current evidence regarding its diagnostic, prognostic, and predictive roles in oncology, with emphasis on its clinical applicability, limitations, and future perspectives. Elevated baseline concentrations of CYFRA 21-1 consistently correlate with greater tumor burden, advanced stage, and poorer survival in cancers such as non–small cell lung cancer, head and neck squamous carcinoma, esophageal, colorectal, breast, thyroid, and urothelial tumors. Serial measurement provides additional clinical insight, as reductions during treatment reflect therapeutic response, whereas rising levels may precede radiologic or clinical relapse. Despite these strengths, limited sensitivity in early-stage disease, biological heterogeneity, and lack of assay standardization currently restrict universal application. Integrative approaches combining CYFRA 21-1 with complementary tumor markers, inflammatory indices, or molecular assays show improved diagnostic and prognostic performance, underscoring its potential as part of multimarker algorithms rather than a stand-alone test. Ongoing efforts to harmonize assays, define reference intervals, and evaluate kinetic behavior in prospective cohorts are essential for translation into practice. Ultimately, CYFRA 21-1 represents a biologically grounded, minimally invasive biomarker capable of enhancing personalized oncology by refining risk stratification, guiding therapeutic decisions, and enabling earlier detection of relapse. Continued validation and clinical integration may establish CYFRA 21-1 as a key component in the evolving landscape of evidence-based cancer management.